Performance Improvement of Existing Three Phase Synchronous Reluctance Machine: Stator Upgrading to 5-Phase With Combined Star-Pentagon Winding - Kotb B. Tawfiq; Mohamed N. Ibrahim; E. E. El-Kholy; Peter Sergeant (IEEE Access, 2020)
This paper investigates the performance of 3-phase synchronous reluctance machines (SynRMs) when upgrading their stator to 5-phase, keeping the same rotor. The design of the 5-phase stator has been optimized to select the optimal dimensions of the slots and teeth. Moreover, a combined star-pentagon winding is employed to further improve the machine performance. Different winding configurations have been studied and compared using 2D Ansys Maxwell transient simulations. It is observed that at optimal current angle and rated current, the average torque is increased by 17.41% when changing the 3-phase stator with the proposed 5-phase one. In addition, the efficiency of the 5-phase SynRM is increased by about 0.8% compared to 3-phase SynRM. At 3 times the rated speed, the torque and efficiency are significantly increased by around 33% and 3.5% respectively. Moreover, the 5-phase SynRM shows a superior performance in the faulty case with one phase opened. It works at 98.84% of the rated torque of the healthy 3-phase machine, whereas the 3-phase machine works at only 43.35% with huge torque ripple (228%). Finally, an experimental validation using the reference 3-phase machine has been done.